التخطيط الاستراتيجي ودوره في تحسين تطبيق تكنولوجيا التعليم بوزارة التعليم التقني في ليبيا (Comprehensive Journal of Science, 2025)
The Technology has an increasing impact on all areas of life, including the education sector, and requires developing countries to emulate developed countries and integrate technology into their education systems. Although relatively late, the Libyan government finally responded to this challenge by investing heavily in rebuilding the education system and launching a national plan to integrate Information and Communication Technology (ICT) into education. In addition, there are plans to create virtual campuses in many universities and colleges in order to provide students and teachers with the most advanced platform. This paper introduces the background of Libyan higher education, describes the current applications of ICT and e-learning in Libyan higher education, and discusses the issues that need to be considered and resolved when introducing ICT into learning and teaching, including technical infrastructure, curriculum development, cultural and language aspects and management support.
Keywords: Strategic planning, educational technology, E-Learning